2001
DOI: 10.1111/1467-9280.00397
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Affects Emotion Through Cognition

Abstract: Determining how, cognition and emotion interact is pivotal to an understanding of human behavior and its disorders. Available data suggest that changes in emotional reactivity and behavior associated with drinking are intertwined with alcohol's effects on cognitive processing. In the study reported here, we demonstrated that alcohol dampens anticipatory fear and response inhibition in human participants not by directly suppressing subcortical emotion centers, as posited by traditional tension-reduction theorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
159
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(173 citation statements)
references
References 21 publications
10
159
4
Order By: Relevance
“…It is well deficit disorder [47]. Alpha activity, especially in alpha2, has also E known that the parietal lobes play a fundamental roll in orientation and selective attention [45], that beta activity has been associated with vigilance and selective attention [18,46], and that a decrease in this band has been observed in psychopathological states, such as attention cognitive process that has been shown to be sensitive to the effects of alcohol, so our EEG data are congruent with the findings of several other studies that have demonstrated that alcohol has a deleterious effect on attention [3,50], and reduces cortical arousal [51].…”
Section: Discusupporting
confidence: 89%
“…It is well deficit disorder [47]. Alpha activity, especially in alpha2, has also E known that the parietal lobes play a fundamental roll in orientation and selective attention [45], that beta activity has been associated with vigilance and selective attention [18,46], and that a decrease in this band has been observed in psychopathological states, such as attention cognitive process that has been shown to be sensitive to the effects of alcohol, so our EEG data are congruent with the findings of several other studies that have demonstrated that alcohol has a deleterious effect on attention [3,50], and reduces cortical arousal [51].…”
Section: Discusupporting
confidence: 89%
“…Fillmore and Selst (2002) showed that alcohol reduces the capacity to process information necessary for the execution and suppression of responses in dual-task, but not singletask, conditions. Finally, Curtin, Patrick, Lang, Cacioppo, and Birbaumer (2001) showed that, during intoxication, reductions in fear response (assessed via startle potentiation) occurred only under dual-stimulus conditions and coincided with reduced attentional processing of threat cues as evidenced by brain responses (indexed via P3 ERPs). Thus, overall, our results fit very well with such findings and the general view that alcohol consumption affects the processing of unattended information by reducing the resources available to process them.…”
Section: Discussionmentioning
confidence: 91%
“…Affix two shock electrodes with standard medical tape to the participant's hand (e.g., distal phalanges of index and ring fingers of the hand) [33][34][35] . 2.…”
Section: Shock Tolerance Threshold Assessmentmentioning
confidence: 99%